The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/pm-07-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Do audit committee structure increases influence the level of voluntary corporate governance disclosures?

Abstract: Purpose The purpose of this paper is to provide an insight into the voluntary corporate governance disclosure and AC practices among Malaysian property listed companies. Along with that, the influence of AC characteristics on voluntary corporate governance disclosure was also examined. Design/methodology/approach The study used the content analysis of annual reports to extract voluntary corporate governance disclosures and audit committee (AC) practices. The relationship between voluntary corporate governanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 53 publications
(60 reference statements)
3
28
0
1
Order By: Relevance
“…More the number of audit committee members, the company will improve the information disclosure (Ho and Wong 2001). The results of the prior study showed that the size of the audit committee has a significant positive effect on disclosure (Li et al 2012, Li et al 2008, Madi et al 2014; positively and significantly influence the voluntary disclosure of corporate governance (Talpur et al 2018); does not affect risk disclosure (Elzahar and Hussainey 2012). The next hypothesis in this paper is as follows:…”
Section: Size Of the Audit Committee And Corporate Risk Disclosurementioning
confidence: 85%
See 4 more Smart Citations
“…More the number of audit committee members, the company will improve the information disclosure (Ho and Wong 2001). The results of the prior study showed that the size of the audit committee has a significant positive effect on disclosure (Li et al 2012, Li et al 2008, Madi et al 2014; positively and significantly influence the voluntary disclosure of corporate governance (Talpur et al 2018); does not affect risk disclosure (Elzahar and Hussainey 2012). The next hypothesis in this paper is as follows:…”
Section: Size Of the Audit Committee And Corporate Risk Disclosurementioning
confidence: 85%
“…The existence of an audit committee is significant in increasing the value of annual reports and reducing information asymmetry (Talpur et al 2018) and is part of the internal control system in corporate governance (Al-Maghzom et al 2016). Cotter and Silvester (2008) stated the supervisory function is not only crucial in the structure and composition of the council, but also for committees of business entity, especially in decision making.…”
Section: Size Of the Audit Committee And Corporate Risk Disclosurementioning
confidence: 99%
See 3 more Smart Citations